Performance of broiler starters fed varying levels of dietary methionine (2012)
One hundred and fifty broiler chicks (Arbor acre breed) were used to determine responses of broiler starters to varying levels of dietary methionine. The chicks were divided into 5 treatment groups consisting of 6 replicates of five chicks each. The chicks were kept in floor pens. The study lasted for 28 days and was conducted at the Teaching and Research Farm of the University of Ibadan, Nigeria. The performance variables under determination were Weight Gain and Feed Intake. No significant differences (p>0.05) were observed in the Weight Gain values from the different levels of methionine included in the diet. But significant differences (p<0.05) were observed, with Feed Intake values, which did not follow a particular trend.